Santiago de Chile 1968-1972 as an Intellective Ecosystem: Attempt at Theorization and Empirical Example; [Santiago Do Chile 1968-1972 Como Ecossistema Intelectual: Tentativa de Teorização E Exemplo Empírico]; [Santiago de Chile 1968-1972 Como Ecosistema Intelectivo: Intento de Teorización y Ejemplo Empírico] - Deves-Valdes, E (Editora Universitaria da PUCRS, 2025)
It is about explaining a fact as unusual as it is important: that an intellectual community from a peripheral city, during a very short period of time (Santiago de Chile 1968-1972) has been transformed into one of the world capitals of thought, generating and exporting some of the most influential eidetic expressions (dependentism, liberationism, social-“e-clacism”, socialist Christianity and almost immediately the Chilean version of neoliberalism), while reflecting on the possibilities of replicating similar situations. For this, the notion of “intellective ecosystem” is formulated. Five hypotheses are developed, rather than tested, that would allow us to understand various ways to explain the creativity boom, in a dynamic that goes beyond the ecosystem itself. The space is mapped, pointing out the most important institutional groups, highlighting in each case the eidetic expressions and figures. The relationships that articulated these places are established, allowing the circulation of ideas, as well as the relationships between the inside and outside of the ecosystem, focusing importantly on exogamy, on the ways of receiving ideas and foreign and intellectual figures. Chileans with recent postgraduate degrees abroad. Finally, an attempt is made to account for the exceptionality that allowed this explosion of creativity and good reception of ideas that emerged in Santiago in other intellectual ecosystems in the world. © 2025, Editora Universitaria da PUCRS. All rights reserved.